1978
DOI: 10.1002/hlca.19780610533
|View full text |Cite
|
Sign up to set email alerts
|

Chemically modified silicon dioxide surfaces. Wetting properties of compact n‐alkyl‐dimethylsiloxy layers, and their mixed surface crystals. The Question of Wetting of Molecularly Rough and of Swollen Surfaces

Abstract: SummaryBy means of contact angle measurements, it has been shown that compact alkyl-dimethyl-doxy layers can be obtained on the surface of acid leached glass using the method previously developed for fume silica. Subsequently, a series of densest possible alkyl-dimethylsiloxy layers were prepared having non-branched alkyl substituents, CZH2z+1, (with z = 1, 2, 3, 6 , 10, 14, 18 and 22) and wetting angles were measured as a function of the temperature. On surfaces coated with longer alkyl substituents the forma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

1978
1978
2003
2003

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(12 citation statements)
references
References 34 publications
1
11
0
Order By: Relevance
“…If the solute alkyl chain is sorbed along a bristle, then a discontinuity in the plot Ed vs. nc should be expected when nc becomes larger than the critical value depending on the length of the bonded moieties. Although such a solute ligand association is entropically unfavorable, Kovats and co-workers have shown that it does exist (19). This is also in agreement with the concept of the critical chain length introduced by Berendsen et al (12).…”
supporting
confidence: 84%
See 1 more Smart Citation
“…If the solute alkyl chain is sorbed along a bristle, then a discontinuity in the plot Ed vs. nc should be expected when nc becomes larger than the critical value depending on the length of the bonded moieties. Although such a solute ligand association is entropically unfavorable, Kovats and co-workers have shown that it does exist (19). This is also in agreement with the concept of the critical chain length introduced by Berendsen et al (12).…”
supporting
confidence: 84%
“…The magnitudes of the steps are obtained by extrapolating the two lines corresponding to the plateau regions and by drawing a vertical line at the inflection point of the step. They are approximately [15][16][17][18][19][20] cal/mol with a precision of 20-30%. The observation of Figures 3D and 4 also reveals that there is no step with the C4 and the polymeric C18 phases.…”
Section: Resultsmentioning
confidence: 99%
“…The longer chain alkylsilane derivatives are less rigid, more liquidlike, and thus smoother surfaces at the molecular level. The effect of molecular roughness on contact angle (not hysteresis) has been discussed in the literature but has not been demonstrated.
2 Contact angle hysteresis as a function of chain length of grafted n -alkyldimethylsilane: CH 2 I 2 (·); C 16 H 34 (▴); (a) toluene, room temperature; (b) toluene, 60−70 °C; (c) vapor phase, 60−70 °C.
…”
Section: Resultsmentioning
confidence: 99%
“…We have previously reported the synthesis of a series of 2,5and 5,6-dihalonicotinic acids of potential medicinal interest (1)(2)(3)(4)(5). As an extension of that work, we now wish to report the preparation and characterization of the methyl esters (I-VIII) of eight of the aforementioned acids.…”
Section: Methodsmentioning
confidence: 99%